The issue of mud wa azwah and its application in the mixed assets susuk trading - Burhanuddin, Muhammad; Awang Hamat, Mohd Afandi (2018)
The main goal of this study to investigate the mixed assets Sukuk tradability regarding the issue of Mud wa Azwah, and the legal maxim have been originated from the Quran, Sunnah, Ijma, Qiyas and tradition. Some reasons may lead to the application of this legal maxim in the mixed assets Sukuk trading, that have been explained and distinguished whether what is included in the contract of sale, based on Mud wa Azwah as well as what can be accepted in its auxiliaries through applying the objectives to facilitate and to stop hardship. Moreover, Four Islamic laws and modern jurists have presented a solutions to deal with the mixed assets Sukuk trading of money, debt, right and wealth, regards to the principle of Mud wa Azwah, However, the study conducts the inductive approach; to collect the research material and data related to the four schools of Islamic laws, the opinions of modern jurists on the trading of mixed assets sukuk. In addition, the study has performed analytical approach, to understand basic concepts and elements in three stages: interpretation, criticism and exploration among them; in terms of jurisprudence and contemporary financial and economic studies, resolution of the Islamic financial institution and recommendations. In addition, the study has found out that the trading of mixed assets Sukuk in the light of the legal maxim of Mud wa Azwah with its terms and conditions is permissible based on Fiqhi studies and Usulis principles. Finally, the research has concluded with a resolution of OIC International Fiqh Academy in dealing with mixed assets Sukuk trading in the light of the legal maxim of Mud wa Azwah.